Superoxide Anion Chemistry—Its Role at the Core of the Innate Immunity - Andrés, Celia María Curieses; Pérez de la Lastra, José Manuel; Andrés Juan, Celia; Plou, Francisco J.; Pérez-Lebeña, Eduardo (International journal of molecular sciences, 2023)
Classically, superoxide anion O2•− and reactive oxygen species ROS play a dual role. At the physiological balance level, they are a by-product of O2 reduction, necessary for cell signalling, and at the pathological level they are considered harmful, as they can induce disease and apoptosis, necrosis, ferroptosis, pyroptosis and autophagic cell death. This revision focuses on understanding the main characteristics of the superoxide O2•−, its generation pathways, the biomolecules it oxidizes and how it may contribute to their modification and toxicity. The role of superoxide dismutase, the enzyme responsible for the removal of most of the superoxide produced in living organisms, is studied. At the same time, the toxicity induced by superoxide and derived radicals is beneficial in the oxidative death of microbial pathogens, which are subsequently engulfed by specialized immune cells, such as neutrophils or macrophages, during the activation of innate immunity. Ultimately, this review describes in some depth the chemistry related to O2•− and how it is harnessed by the innate immune system to produce lysis of microbial agents.